Dynamics and structural behavior of water in large confinement with planar amorphous walls - Ferrara, Carlos Gastón (2017)
We study the structure and dynamics of liquid water confined between planar amorphous walls using molecular dynamics (MD) simulations. We report MD results for systems of more than 23 000 SPC/E water molecules confined between two hydrophilic or hydrophobic walls, separated by distances of about 15 nm. We find that the walls induce ordering of the liquid and slow down the dynamics, affecting the properties of the confined water up to distances of about 8 nm at 275 K. We quantify this influence by computing dynamic and static penetration lengths and studying their temperature dependence. Our results indicate that in the temperature range considered, hydrophobic walls perturb static properties over larger lengths compared to hydrophilic walls. We also find opposite temperature trends in the dynamic penetration lengths, with hydrophobic walls increasing their range of influence on increasing the temperature.